Hadith #2238 - Sunan Ibn Majah - Abu Bakr al-Hanfi عبد الكبير بن عبد المجيد- أبو بكر الحنفي; Abu Yahya al-Makki أبو يحيى المكي; al-Hythm bin Rafa'i al-Hnfy الهيثم بن رافع الحنفي; Umar ibn al-Khattab; Yahya bin Hakeem al-Maquuam يحيى بن حكيم المقوم (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘The lost animal of the Muslim may lead to the burning flame of Hell.’ ”
Grade: